OpenSource Lab‐on‐a‐Chip Physiometer for Accelerated Zebrafish Embryo Biotests. Issue 1 (16th February 2018) - Akagi, Jin; Hall, Chris J.; Crosier, Kathryn E.; Cooper, Jonathan M.; Crosier, Philip S.; Wlodkowic, Donald
Abstract: Zebrafish ( Danio rerio ) embryo assays have recently come into the spotlight as convenient experimental models in both biomedicine and ecotoxicology. As a small aquatic model organism, zebrafish embryo assays allow for rapid physiological, embryo‐, and genotoxic tests of drugs and environmental toxins that can be simply dissolved in water. This protocol describes prototyping and application of an innovative, miniaturized, and polymeric chip‐based device capable of immobilizing a large number of living fish embryos for real‐time and/or time‐lapse microscopic examination. The device provides a physical address designation to each embryo during analysis, continuous perfusion of medium, and post‐analysis specimen recovery. Miniaturized embryo array is a new concept of immobilization and real‐time drug perfusion of multiple individual and developing zebrafish embryos inside the mesofluidic device. The OpenSource device presented in this protocol is particularly suitable to perform accelerated fish embryo biotests in ecotoxicology and phenotype‐based pharmaceutical screening. Curr. Protoc. Cytom . 67:9.44.1‐9.44.16. © 2014 by John Wiley & Sons, Inc.